Comparison of the sensitizing effects of cocaine and ethanol on histone deacetylase isoforms in the rat brain. Issue 6 (7th April 2021) - Xu, Shijie; Koo, Ja Wook; Kang, Ung Gu
Abstract : Behavioral sensitization, an animal model of drug addiction, persists for a prolonged period after repeated exposure to drugs of abuse. The persistence of an addiction behavioral phenotype suggests long-lasting changes in gene regulation at the epigenetic level. We measured the expression of histone deacetylases (HDACs) isoforms in the prefrontal cortex and dorsal striatum following the development of sensitization to cocaine (15 mg/kg, administered five times) and ethanol (0.5 g/kg, administered 15 times) to investigate the epigenetic changes that mediate sensitization. Animals sensitized to ethanol exhibited augmented locomotor activity in response to the cocaine challenge. Similarly, those sensitized to cocaine exhibited increased locomotor activity in response to an ethanol challenge. These findings indicate cross-sensitization between ethanol and cocaine and suggest that a common molecular mechanism underlying the cross-sensitization. In animals sensitized to cocaine or ethanol, mRNA levels of class II HDACs (HDAC4 and HDAC5) were decreased in the prefrontal cortex and dorsal striatum, whereas acute treatments with either drug had no effect on the expression of class II HDACs. By contrast, class I HDACs (HDAC1 and HDAC2) responded to the acute cocaine challenge, whereas sensitization itself did not have a consistent effect on class I HDAC levels. These findings support the hypothesis of a common epigenetic mechanism underlying persistent behavioral sensitization induced by different drugs, which may be mediated by the altered expression of class II HDACs.